Math, asked by mav31, 1 year ago

simplify...

(3  +   \sqrt{2} )(2 +  \sqrt{2)}
simplify...

(3  + \sqrt{3} )(3 -  \sqrt{3} )
simplify...

( \sqrt{5}  +  \sqrt{2} ) {}^{2}
simplify..

 (\sqrt{5}  -  \sqrt{2} )(  \sqrt{5}  -  \sqrt{2} )

Answers

Answered by Anonymous
54

Solution :

1. (3+√2)(2+√2)

By multiplying horizontally,

=> 3(2+√2) + √2(2+√2)

=> 6 + 3√2 + 2√2 + 2

=> 8 + 5√2

_______________________

2. (3+√3)(3-√3)

By using - = (a+b)(a-b)

=> (3)² - (√3)²

=> 9 - 3

=> 6

_______________________

3. (√5+√2)²

By using (a+b)² = + + 2ab

=> (√5)² + (√2)² + (2)(√5)(√2)

=> 5 + 2 + 2√10

=> 7 + 2√10

_______________________

4. (√5-√2)(√5-√2)

By using (a-b)² = + - 2ab

=> (√5-√2)²

=> (√5)² + (√2)² - (2)(√5)(√2)

=> 5 + 2 - 2√10

=> 7 - 2√10

_______________________

You can solve these type of questions by using Identities. It makes question easy to solve.

Answered by Anonymous
25

Step-by-step explanation:

(i)(3 +  \sqrt{2} )(2 +  \sqrt{2} ) \\  \\  = 3(2 +  \sqrt{2} ) + 2(2 +  \sqrt{2} ) \\  \\  = 6 + 3 \sqrt{2}  + 4 + 2 \sqrt{2}  \\  \\  = 10 + 5 \sqrt{2}

(ii)(3 +  \sqrt{ 3} )(3 -  \sqrt{3} ) \\  \\  =  {(3)}^{2}  -  {( \sqrt{3} )}^{2}   \\  \\  = 9 - 3 \\  \\  = 6

(iii) {( \sqrt{5}  +  \sqrt{2}) }^{2}  \\  \\  =  {( \sqrt{5} )}^{2}  +  {( \sqrt{2}) }^{2}  + 2( \sqrt{5} )( \sqrt{2} ) \\  \\  = 5 + 2 + 2 \sqrt{10}  \\  \\  = 7 + 2 \sqrt{10}

(iv)( \sqrt{5}  -  \sqrt{2} )( \sqrt{5}  -  \sqrt{2} ) \\  \\  =  {( \sqrt{5} -  \sqrt{2} ) }^{2}  \\  \\  =  {( \sqrt{5}) }^{2}  +  {( \sqrt{2} )}^{2} - 2( \sqrt{5}  )( \sqrt{2} ) \\  \\  = 5 + 2 - 2 \sqrt{10}  \\  \\  = 7 - 2 \sqrt{10}

Similar questions